Step Up of Rural Women Entrepreneurship in East Singhbhum - Kumari, Kamini (Nepalese Journal of Business, 2025)
Why are women entrepreneur’s day celebrated? There is no such term as “men entrepreneurs” or the top 50 powerful CEOs globally. But for women there is a separate category for top 50 powerful CEOs. It’s still rare to have female business leaders in the 21st century or we can say that women are breaking the stereo type. Now, there is a need to think about the acceleration of woman entrepreneurship management. Rural Women are now increasingly run their own business yet their entrepreneurial potential, managerial skill and socio economic contribution largely neglected. Women entrepreneurship development is the instrument of women empowerment. Women are becoming socially empowered and economically empowered through business ownership. Women Entrepreneurship is gaining is gaining importance in India in the wake of globalization and economic liberalization. The institutional and policy framework for developing entrepreneurial skill, providing vocational education and training has widened the horizon of for economic development of Women. Women entrepreneurs tend to be self-dependent, self-motivated and self-directed. On the other hand, empowerment of rural women is also very significant. Economic empowerment of rural women will lead to the development of our country. And it is very necessary to give keen attention over his empowerment of women in the rural areas for the real development of our country in all spheres. Women entrepreneurship is important for women’s position in society and economic of women will lead to development of family, community and country. The present study focuses on parameters to be focused to enhance the entrepreneurial skill of rural women in East Singhbhum and in turn their empowerment.